Genome‐wide survey by ChIP‐seq reveals YY1 regulation of lincRNAs in skeletal myogenesis. (13th August 2013) - Lu, Leina; Sun, Kun; Chen, Xiaona; Zhao, Yu; Wang, Lijun; Zhou, Liang; Sun, Hao; Wang, Huating
<x xml:space="preserve">Abstract</x> Skeletal muscle differentiation is orchestrated by a network of transcription factors, epigenetic regulators, and non‐coding RNAs. The transcription factor Yin Yang 1 (YY1) silences multiple target genes in myoblasts (MBs) by recruiting Ezh2 (Enhancer of Zeste Homologue2). To elucidate genome‐wide YY1 binding in MBs, we performed chromatin immunoprecipitation (ChIP)‐seq and found 1820 specific binding sites in MBs with a large portion residing in intergenic regions. Detailed analysis demonstrated that YY1 acts as an activator for many loci in addition to its known repressor function. No significant co‐occupancy was found between YY1 and Ezh2, suggesting an additional Ezh2‐independent function for YY1 in MBs. Further analysis of intergenic binding sites showed that YY1 potentially regulates dozens of large intergenic non‐coding RNAs (lincRNAs), whose function in myogenesis is underexplored. We characterized a novel muscle‐associated lincRNA (Yam‐1) that is positively regulated by YY1. Yam‐1 is downregulated upon differentiation and acts as an inhibitor of myogenesis. We demonstrated that Yam‐1 functions through in cis regulation of miR‐715, which in turn targets Wnt7b. Our findings not only provide the first genome‐wide picture of YY1 association in muscle cells, but also uncover the functional role of lincRNA Yam‐1.